1996
DOI: 10.1164/ajrccm.154.1.8680689
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide is decreased in asthmatic patients by an inhibitor of inducible nitric oxide synthase.

Abstract: Exhaled nitric oxide (NO) may be derived from constitutive NO synthase (NOS) in normal airways, but the increased concentration in asthma is likely to be derived from inducible NOS expressed in inflamed airways. To investigate this, we administered a nonselective NOS inhibitor, NG-nitro-L-arginine methyl ester (L-NAME), and a selective inhibitor of inducible NOS, aminoguanidine, by nebulization in a double-blind, placebo-controlled manner in both normal subjects and subjects with asthma. L-NAME resulted in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
80
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 0 publications
8
80
0
1
Order By: Relevance
“…In the absence of airway inflammation, FeNO levels represent constitutive NO. 11,22 Subjects with depression also have low levels of plasma and platelet NO. 23,24 The low systemic levels of NO have been postulated to be responsible for the increased risk of cardiovascular events observed in subjects with depression, 24 as NO produces vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of airway inflammation, FeNO levels represent constitutive NO. 11,22 Subjects with depression also have low levels of plasma and platelet NO. 23,24 The low systemic levels of NO have been postulated to be responsible for the increased risk of cardiovascular events observed in subjects with depression, 24 as NO produces vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques that permit separate measurement of the airway and alveolar components of FeNO would be useful in this context to address the hypothesis that smoking primarily alters airway respiratory epithelial production of FeNO [47]. Experiments using intravenous and inhaled inhibitors of the different isoforms of NOS would also be useful to delineate the relative contributions of neural NOS1, airway NOS2 and vascular NOS3 to the difference in FeNO between older smokers and nonsmokers [15,48].…”
Section: Discussionmentioning
confidence: 99%
“…FeNO levels increase after smoking cessation but not to normal levels [2,6,10], which suggests that smoking-related declines in FeNO may be associated with permanent lung damage. As respiratory epithelium is the likely source of most FeNO [11][12][13][14][15] and is damaged by chronic smoke exposure [16][17][18][19][20], smoking-related declines in FeNO may be a marker of airway epithelial damage.…”
mentioning
confidence: 99%
“…The increased presence of NOS II in the inflamed lung has been shown to contribute to complement-induced pulmonary injury, 40 lung transplant rejection, 41 and airway hyperresponsiveness in asthma. 42,43 Conversely, others 44 have shown that increased nitric oxide production by lung epithelial cells protects these cells from polymorphonuclear-cell-mediated injury. Increased nitric oxide Figure 6.…”
Section: Discussionmentioning
confidence: 99%